2008
DOI: 10.1007/s10067-008-1011-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum and synovial fluid levels of p40 IL12/23 in spondyloarthropathy patients

Abstract: IL-23 is the main inductor in Th17 polarization of naive T cells, inducing IL-17 production. IL-17 has been demonstrated to be elevated in ankylosing spondylitis (AS). The p40 subunit is common to IL-12 and IL-23. We assessed serum and synovial levels of p40 IL12/23 in spondyloarthropathy (SpA) patients and the evolution under anti-TNF. SpA patients fulfilling ESSG criteria were included. Healthy volunteers served as controls. P40 IL12/23 was assessed using Human Quantikine ELISA (R&D Systems), and at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 10 publications
3
30
2
Order By: Relevance
“…There are a limited number of studies on IL-23 levels in AS. A recent study found increased IL-23 in AS [10], but other studies reported contradicting results [8,11]. In this study, the concentrations of both IL-12 and IL-23 were significantly higher in AS patients; we also found AS patients had significantly higher TGF-b and IL-6 concentrations, which are responsible for the differentiation of Th-17 cells [18].…”
Section: Discussioncontrasting
confidence: 34%
See 1 more Smart Citation
“…There are a limited number of studies on IL-23 levels in AS. A recent study found increased IL-23 in AS [10], but other studies reported contradicting results [8,11]. In this study, the concentrations of both IL-12 and IL-23 were significantly higher in AS patients; we also found AS patients had significantly higher TGF-b and IL-6 concentrations, which are responsible for the differentiation of Th-17 cells [18].…”
Section: Discussioncontrasting
confidence: 34%
“…Recent studies suggest interleukin-23 receptor (IL-23R) is one of the major generic factors involved in one's susceptibility to AS [1][2][3][4]. In accordance with this observation, recent studies focused on the T helper 17 (Th17) axis in patients with AS or spondyloarthropathy (SpA) [5][6][7][8][9][10][11]. However, the available data is still limited and additional information is needed.…”
Section: Introductionmentioning
confidence: 81%
“…Later studies showed that patients with SpA have elevated IL12 and IL23 levels in their synovial fluid and peripheral blood [21]. Elevated IL23 levels have been linked to the presence of human leukocyte antigen B27 (HLA-B27) positivity among these patients [22].…”
Section: Il23 and Psoriatic Arthritismentioning
confidence: 99%
“…Previous studies did not demonstrate elevated levels of p40 IL-23 in the serum of AS patients, compared with controls, whereas, in some of them, synovial fluid levels were higher than serum levels [7]. This gives the central role to p40 IL-23 in the pathophysiological axis, and a potential theraputic target in AS.…”
Section: Sirmentioning
confidence: 78%